Humic substances increase tomato tolerance to osmotic stress while modulating vertically transmitted endophytic bacterial communities - Lengrand, Salomé; Dubois, Benjamin; Pesenti, Lena; Debode, Frederic; Legrève, Anne (Frontiers in Plant Science, 2024)
While humic substances (HS) are recognized for their role in enhancing plant growth under abiotic stress by modulating hormonal and redox metabolisms, a key question remains: how do HS influence the microbiota associated with plants? This study hypothesizes that the effects of HS extend beyond plant physiology, impacting the bacterial endophytic community. To explore this, we investigated the combined and individual impacts of HS and osmotic stress on tomato plant physiology and roots endophytic communities. Tomatoes were grown within a sterile hydroponic system which allowed to focus on seed-transmitted endophytic bacteria. Moreover, sequencing the 16S-ITS-23S region of the rrn operon (˜4,500 bp) in a metabarcoding assay using the PNA-chr11 clamp nearly eliminated reads assigned to Solanum lycopersicum and allowed species-level identification of these communities. Our findings revealed that HS, osmotic stress and their combined application induce changes in bacterial endophytic communities.Osmotic stress led to reduced plant growth and a decrease in Bradyrhizobium sp., while the application of HS under osmotic stress resulted in increased tomato growth, accompanied by an increase in Frigoribacterium sp., Roseateles sp., and Hymenobacter sp., along with a decrease in Sphingomonas sp. Finally, HS application under non-stress conditions did not affect plant growth but did alter the endophytic community, increasing Hymenobacter sp. and decreasing Sphingomonas sp. This study enhances understanding of plant-endophyte interactions under stress and HS application, highlighting the significance of the verticallytransmitted core microbiome in tomato roots and suggesting new insights into the mode of action of HS used as biostimulant.